Factors Affecting Customer Interest in KPR iB Griya Housing Financing at PT Bank Sumut, Sibolga Syariah Branch - Mutiara, Mutiara Manalu; Nasution, Yenni Samri Juliati; Syakir, Ahmad (Amkop Management Accounting Review (AMAR), 2025)
This research is motivated by the lack of customer interest in the iB Griya KPR financing product at PT. Bank Sumut, Sibolga Syariah Branch, where in the last 4 years through a pre-survey there has been no customers in this financing. Therefore, the purpose of this study is to find and analyze the factors that influence customer interest in iB Griya KPR financing. The research method applied is quantitative and the analysis used is multiple linear regression as an analysis tool. The proof of the hypothesis used is through significant testing. The sample of this study uses random sampling, namely by choosing freely among savings customers at PT. Bank SUMUT, Sibolga Syariah Branch from the beginning of 2021-2025. The independent variable in this study is customer interest. While data analysis uses SPSS 20, Classical Assumption Test, Multiple Linear Regression and Hypothesis Testing to test the data statistically. The results of this study indicate that price, promotion and location influence customer interest in iB Griya KPR financing at PT. Bank Sumut, Sibolga Syariah Branch. It can be concluded that efforts to increase consumer interest can be done by paying attention to appropriate pricing strategies, implementing effective promotions, and selecting an ideal location to maximize the attractiveness of the products or services offered, so that it can increase purchasing decisions and consumer loyalty.